2015
DOI: 10.1007/s00125-015-3836-9
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3 is essential for mitochondrial bioenergetics during adipocyte remodelling in mice

Abstract: Aims/hypothesis Adipose tissue is a highly versatile system in which mitochondria in adipocytes undergo significant changes during active tissue remodelling. BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3) is a mitochondrial protein and a known mitochondrial quality regulator. In this study, we investigated the role of BNIP3 in adipocytes, specifically under conditions of peroxisome proliferator-activated receptor-γ (PPARγ)-induced adipose tissue remodelling. Methods The expression of BNIP3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…We substantiate their data and also provide evidence supporting the necessity of C/EBPα in the regulation of Bnip3 expression. Similar to our results, Choi et al also reported that Bnip3 is critical for adipocyte mitochondrial bioenergetics, but they ascribed this to a Bnip3-related increase in mitochondrial biogenesis (49). We have exhaustively analyzed various indices for mitochondrial content but were unable to find disparities between shCtrl and Bnip3-KD adipocytes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We substantiate their data and also provide evidence supporting the necessity of C/EBPα in the regulation of Bnip3 expression. Similar to our results, Choi et al also reported that Bnip3 is critical for adipocyte mitochondrial bioenergetics, but they ascribed this to a Bnip3-related increase in mitochondrial biogenesis (49). We have exhaustively analyzed various indices for mitochondrial content but were unable to find disparities between shCtrl and Bnip3-KD adipocytes.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Choi et al (49) validated Bnip3 as a direct transcriptional target of PPARγ in adipose tissue. We substantiate their data and also provide evidence supporting the necessity of C/EBPα in the regulation of Bnip3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…While parkin may be best characterized in the context of mitophagy, several other proteins appear to function in a somewhat similar manner, with their recruitment to mitochondria mediating degradation of the organelle. The role of one such protein, BNip3, was recently investigated in a similar context to the present manuscript . The authors observed an increase in BNip3 expression in 3T3‐L1 adipocytes following rosiglitazone treatment, while the adipose tissues of high‐fat‐diet‐fed and db/db mice exhibited decreased BNip3 expression.…”
Section: Discussionmentioning
confidence: 52%
“…The images were analyzed with ImageJ version 1.49v software (http://imagej.nih.gov/ij). Electron microscopic image analysis was performed according to a previous report (21).…”
Section: Histological Analysismentioning
confidence: 99%
“…Western blot was performed as previously described (21) with anti-PDX-1, anti-GLUT2, and anti-GAPDH (Sigma-Aldrich) antibodies.…”
Section: Western Blotmentioning
confidence: 99%